Reduction of Saturated Fat in Dark Chocolate using Sacha Inchi (Plukenetia volubilis) Oil Oleogel - Ishak, Izzreen; Ismail, Nur Ezzatul Balqish; Yahaya, Nabilah Shahiqah; Khaironi, Johari; Musa, Nafisah; Teh, Arnida Hani; Ghani, Maaruf Abd (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This research studied the effectiveness of Sacha Inchi Oil Oleogel (SIOO) as a partial replacement for saturated fat in dark chocolate. Sacha inchi (Plukenetia volubilis) oil is high in polyunsaturated fatty acids (α-linolenic and linoleic acids) and a good source of tocopherols. This study prepared oleogels using sacha inchi oil as a base oil and food-grade beeswax as an oleogelator. Different percentages of SIOO (1%, 2.5% and 5.0%) were added in the dark chocolate. Dark chocolate without SIOO was used as a control. Fatty acid profile, total polyphenols, antioxidant activity and sensory evaluation of the formulated dark chocolates with SIOO were investigated. The incorporation of SIOO significantly (p<0.05) lowered the saturated fat and increased the polyunsaturated fatty acids in dark chocolate samples. This study also showed that the total polyphenols and antioxidant activity of dark chocolates enriched with 2.5 and 5.0% SIOO were significantly higher (p<0.05) than the other chocolate samples. Sensory evaluation showed that control and dark chocolates added with SIOO (1% and 2.5%) received similar scores for all sensory attributes. However, the highest concentration of SIOO decreased significantly (p<0.05) the scores for the taste and overall acceptability of dark chocolate. Therefore, the enrichment of sacha inchi oil oleogel as a functional ingredient could reduce the saturated fat and increase the polyunsaturated fatty acids and antioxidant activity of the formulated dark chocolate, which is well-accepted by consumers.